KNOWLEDGE AND SELF-CARE PRACTICES AMONG DIABETIC PATIENTS-A CASE STUDY OF THIKA LEVEL 5 HOSPITAL, KENYA - Wamucii, Eunice Gathoni; Kiage, Beatrice; Kyallo, Florence (Journal of Health, Medicine and Nursing, 2020)
Purpose: The main aim of the study was to determine the level of self-care knowledge and practices among diabetic patients in Thika level 5 Hospital. Methodology: Cross-sectional study design was used in this study. The target population included patients living with diabetes seeking medical services at the diabetic clinic at Thika Level V hospital. Being the largest referral hospital that served patients form the entire Kiambu County, the hospital was purposely selected. Simple random sampling technique was used to select 190 respondents among patients visiting the diabetic clinic. Structured questionnaire that was interviewer administered was used to collect data. SPSS version 21 software was used for data analysis. Findings: The mean diabetes knowledge score was 7.7 out of a total of 14 and the mean self-care activities score was 7.6 out of a total of 14, indicating a deficit in a number of key areas in the knowledge and self-management of diabetes. There was statistical significant relationship between patient's level of knowledge of diabetes self-care practices and age (Ï‡2 (4, N=190) = 10.189, p = .037), education level, (Ï‡2 (6, N=190) = 17.861, p = .007) and employment status, (Ï‡2 (6, N=190) = 16.655, p = .011).Statistically significant association was also found between adherence to recommended diabetes self- care practices and age, Ï‡2 (4, N=190) = 4.501, p = .034, education level, Ï‡2 (6, N=190) = 15.616, p = .016, employment status, Ï‡2 (1, N=190) = 3.830, p = .005. Pearson correlation between knowledge of diabetes self-care practices and adherence to diabetes self-care practices was weak in strength and statistically significant r (188) =0.367, p=< 0.01. This implies that the three factors are significant determinants of the level of self-care knowledge and practices among diabetic patients in Thika level V hospital. Unique contribution to theory, practice and policy: The research demonstrated gaps in self-care knowledge and adherence to self-care practices. Moreover patient's level of knowledge hardly translated to good self-care practices. It is hence important to integrate behavioral change theories into the diabetes educational interventions which may facilitate problem solving skills that will enhance the application of acquired knowledge among the diabetic patients. In addition, more research is warranted to explore patients' perceptions and attitude towards the effectiveness of their self-care management so the diabetic education can be tailored according to patients' needs.